Simulation of earthing systems under high impulse conditions - Nor, , N. Mohamad (2006)
Several models of earthing systems under high impulse conditions, which are in satisfactory agreement to the experimental results, have been proposed in previous studies [1-11]. However, these models do not consider for the effects of current rise time as the voltage levels were increased.